Pengaruh Pertumbuhan Ekonomi, Kapitalisasi Pasar, Suku Bunga Bank Indonesia, Inflasi, Dan Volatilitas Harga Saham Sebagai Variable Moderating Terhadap Kinerja Pasar Saham Perbankan Syariah Di Indonesia - kadek_payas suputra; I Gusti Ayu Purnamawati; Desak Nyoman Sri Werastuti (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
ABSTRACT This research purpose to explore and analyze the effect of growth, market capitalization, Bank Indonesia interest rates, and inflation on the stock market performance of Indonesian Islamic banks, moderated by stock price volatility. The method of data collection in this study is the method of documentation. The population of this study is all Islamic banks registered in Indonesia. The samples for this study are islamic banking financial statements and annual reports from the 14 largest Islamic commercial banks in Indonesia. This research approach uses moderate regression analysis analyzed with SPSS. As a result, economic growth has a significant positive effect on stock market performance, market capitalization has a significant positive effect on stock market performance, interest rates have a significant negative effect on stock market performance, Inflation has proven to have a significant negative effect on stock market performance, meanwhile, Stock Price Volatility is able to moderate Economic Growth, Market Capitalization, Interest Rates, Inflation against The Performance of the Indonesian Islamic Banking Stock Market. Keywords: Economic Growth, Market Capitalization, Bank Indonesia Interest Rates, Inflation, Stock Price Volatility, Stock Market Performance